Pelatihan Pembuatan Lilin Aromaterapi Antinyamuk Pada Anggota Fatayat Nu Ranting Purwosari - Nawangsari, Desy; Kurniasih, Khamdiyah Indah; Prabandari, Rani; Fitri, Ely Nurul (Yayasan Inspirasi El Burhani, 2025)
Introduction: Used cooking oil is oil that has been used repeatedly up to 3-4 times frying. The negative impact of used cooking oil if thrown away will become waste and damage the surrounding environment. One of the products of used cooking oil processing is aromatherapy candles and soap. Various forms of aromatherapy have sprung up such as essential oils, candles, incense, soaps and massage oils. People only use candles as a source of lighting when there is no electricity source. The function of candles is not only a lighting aid but is widely used as a room decorator and as a room fragrance, in this case what is commonly used is aromatherapy candles. Objective: The objectives of this activity are (1) Minimizing the disposal of used cooking oil (2) Changing the lifestyle of the community to process used cooking oil waste based on zero waste industry (3) Reducing the disposal of used cooking oil in any place can reduce the risk of groundwater pollution (4) Creating anti-mosquito aromatherapy candle products that have economic value. Method: The method of implementing the activity was carried out by providing material on the utilization of used cooking oil and training in making aromatherapy candle products for mosquitoes. Result: The outputs of this activity are increased knowledge related to products and the risk of contamination to the environment, increased knowledge and skills of partners in making aromatherapy candles. Conclusion: The training on making mosquito-repellent aromatherapy candles from used cooking oil successfully improved participants' knowledge and skills. It supports waste reduction and economic empowerment. Despite challenges in raw material consistency, the program holds potential for sustainability and commercialization.